Analisis Pengaruh Teori Kriminologi Terhadap Reformasi Sistem Pemasyarakatan dalam Penanganan Kejahatan di Indonesia - Kezia Agrarianti Mocodompis (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The development of community dynamics continues to be followed by the development of crime in the community. The Indonesian Correctional System, which is obliged to facilitate crime handling efforts in Indonesia, must continue to develop following the dynamics of society by formulating broadly appropriate crime handling efforts. This research aims to identify the extent to which criminological theories as a science that explains the causes of a crime have and can contribute in providing a point of view on the background and reasons for someone to commit a crime so that then the Indonesian Correctional System can continue to formulate targeted programs to deal with and control crime so that repetition of crime can be avoided. The research will be conducted using a normative juridical method with a qualitative approach. It is hoped that this research can produce recommendations for optimizing the role and influence of criminological theories in the formulation of an optimal Indonesian Correctional System so that the national correctional pattern can have a significant impact in handling and controlling crime in Indonesia.